An ALMA view of 11 dusty star-forming galaxies at the peak of cosmic star formation history. Issue 3 (16th August 2021) - Pantoni, L; Massardi, M; Lapi, A; Donevski, D; D'Amato, Q; Giulietti, M; Pozzi, F; Talia, M; Vignali, C; Cimatti, A; Silva, L; Bressan, A; et al.
ABSTRACT: We present the ALMA view of 11 main-sequence dusty star-forming galaxies (DSFGs) (sub-)millimetre selected in the Great Observatories Origins Survey South (GOODS-S) field and spectroscopically confirmed to be at the peak of cosmic star formation history ( z ∼ 2). Our study combines the analysis of galaxy spectral energy distribution with ALMA continuum and CO spectral emission by using ALMA Science Archive products at the highest spatial resolution currently available for our sample (Δθ ≲ 1 arcsec). We include galaxy multiband images and photometry (in the optical, radio, and X-rays) to investigate the interlink between dusty, gaseous, and stellar components and the eventual presence of AGN. We use multiband sizes and morphologies to gain an insight on the processes that lead galaxy evolution, e.g. gas condensation, star formation, AGN feedback. The 11 DSFGs are very compact in the (sub-)millimetre (median r ALMA  = 1.15 kpc), while the optical emission extends to larger radii (median r H / r ALMA  = 2.05). CO lines reveal the presence of a rotating disc of molecular gas, but we cannot exclude the presence of interactions and/or molecular outflows. Images at higher (spectral and spatial) resolution are needed to disentangle from the possible scenarios. Most of the galaxies are caught in the compaction phase, when gas cools and falls into galaxy centre, fuelling the dusty burst of star formation and the growing nucleus. We expect these DSFGs to be the high-z star-forming counterparts of massive quiescent galaxies. Some features of CO emission in three galaxies are suggestive of forthcoming/ongoing AGN feedback, which is thought to trigger the morphological transition from star-forming discs to early-type galaxies.